The Protection of Human Rights in Indonesia and Hungary: Comparative Legal Perspectives - Melkias Hetharia; Talabos Dávidné Lukács Nikolet (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2025)
Introduction: The protection of human rights (HAM) remains a fundamental challenge in contemporary international law, particularly in bridging the gap between international normative standards and their domestic implementation. Despite both Indonesia and Hungary having ratified core international human rights instruments including the ICCPR and ICESCR and enshrining human rights guarantees within their respective constitutions, significant disparities persist between formal legal commitments and the actual effectiveness of rights protection in practice. Purposes of the Research: This study aims to examine how the doctrines and principles of national law in Indonesia and Hungary construct human rights protection within the framework of harmonization with international legal norms, and to analyze the implications of their differing juridical approaches for the effectiveness of constitutional rights protection in law enforcement practice. Methods of the Research: This research employs a normative legal method with comparative and statute approaches. Results Main Findings of the Research: The findings reveal that Indonesia applies a selective incorporation model rooted in Pancasila, producing adaptive yet volatile protection contingent on political dynamics and institutional commitment, whereas Hungary formally adopts a structural integration model within the European supranational framework but has experienced systematic degradation of rights protection through abusive constitutionalism and democratic backsliding. Both cases demonstrate that the effectiveness of constitutional rights protection is not determined by the sophistication of the legal model chosen, but rather by the quality of the democratic ecosystem, the consistency of judicial interpretation, and sustained institutional commitment across all branches of state power. This study contributes a comparative normative framework that enriches human rights law literature with cross-regional analysis between Southeast Asia and Central Europe.